PENGARUH PEMBERIAN ARANG SEKAM PADI DAN ARANG TEMPURUNG KELAPA TERHADAP PERTUMBUHAN AKAR TANAMAN KACANG PUTIH (Vigna unguiculata) - Murtilaksono, Aditya; Mardhiana; Arzuknani; Apriyani, Mela (AGRO TATANEN | Jurnal Ilmiah Pertanian, 2023)
Kalimantan Island which has problems in soil fertility, namely low pH which can inhibit plant growth so that efforts can be made by adding charcoal as a soil improvement agent. The purpose of this study was to determine the response of white bean roots to the application of rice husk charcoal and coconut shells. The method used in this study is a single factor Randomized Block Design. There were nine treatments, namely A0 (control), A1 (6.25 g rice husk charcoal), A2 (12.5 g rice husk charcoal), A3 (25 g rice husk charcoal), A4 (50 g rice husk charcoal), A5 (6.25 g coconut shell charcoal), A6 (12.5 g coconut shell charcoal), A7 (25 g coconut shell charcoal) and A8 (50 g coconut shell charcoal). The parameters observed in this study were root wet weight, root length, number of roots, number of root hairs, number of root nodules, root volume, and root dry weight. The results of the research obtained were that the dose and type of charcoal had a significant effect on the parameters of root wet weight and root volume. The treatment that had the highest value on the root wet weight parameter was treatment A8 (50 g coconut shell charcoal) with a value of 0.87 g and the treatment that had the highest value on the root volume parameter was treatment A3 (25 g rice husk charcoal) with an average value. the average was 0.75 cm3 but had no significant effect on root length, number of roots, number of root hairs, root nodules and root dry weight.